Ontological Fundamentals for Ethical Management - Heil, Dominik. author. aut Link
XVII, 195 p.
Keywords: The book develops a philosophical foundation to the field of management as an academic discipline using the work of Martin Heidegger as a guiding philosophy. It asks the questions ‘what is a corporation?’ and ‘what is corporate management?’ These two questions are foundational for management thought in general and management ethics in particular. Most other academic fields are in some way defined and guided by a philosophical discourse. This philosophical discourse is largely missing in the field of management thought and education. Without this foundation it can never be clear what actually belongs into a certain academic discipline and what does not. It also therefore lacks a sound and well articulated ontological foundation critical for developing approaches to ethical management. This book seeks to fill this gap and consequently represents an interdisciplinary effort between the academic field of management/business administration and philosophy, which is vital for business ethics.